Analisa Variasi Jumlah Mata Pisau Pada Mesin Pengiris Bawang Merah - Saktisahdan, Tengku Jukdin; Bahari, Alvin (Politeknik Negeri Padang, 2024)
The slicing process of shallots using simple tools remains a major obstacle to increasing production capacity and efficiency in the processing industry. To address these limitations, an analysis of the blade count variation in shallot slicing machines is required to produce more efficient and uniform slices. This study aims to optimize the shallot slicing process, enhance production efficiency, and evaluate machine performance with blade count variations of 2, 3, and 4 blades.The methods employed include documentation, direct experimental observation, and systematic data collection through treatment of experimental variables. The results show that the use of 2, 3, and 4 blades yields slicing capacities of 62 kg/hour, 70 kg/hour, and 78 kg/hour, respectively, with an average slice thickness ranging from 0.8 to 1.1 mm.These findings indicate that the number of blades significantly affects slicing productivity and efficiency, with the 4-blade configuration demonstrating the best performance. This study provides valuable insights for developing more effective and efficient shallot slicing machines, contributing to increased productivity in the shallot processing industry.